2023
DOI: 10.3390/rs15133389
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations of Atmospheric CH4 in Monsoon Asia Detected by Satellite Observations of GOSAT and TROPOMI

Abstract: Space-based measurements, such as the Greenhouse gases Observing SATellite (GOSAT) and the TROPOspheric Monitoring Instrument (TROPOMI) aboard the Sentinel-5 Precursor satellite, provide global observations of the column-averaged CH4 concentration (XCH4). Due to the irregular observations and data gaps in the retrievals, studies on the spatial and temporal variations of regional atmospheric CH4 concentrations are limited. In this paper, we mapped XCH4 data over monsoon Asia using GOSAT and TROPOMI observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…For example, data from the Japanese Greenhouse Gases Observing Satellite (GOSAT) revealed that the global monthly mean CH 4 concentration reached 1873 ppb in March 2023, with a growth rate of 15 ppb year −1 from March 2022 to March 2023 (https://www.gosat.nies.go.jp/recent-global-ch4.html (accessed on 6 July 2023)). Reducing methane emissions can be considered an effective way to quickly mitigate climate change because of methane's shorter lifetime than CO 2 [11]. However, the estimation of methane emissions is influenced by numerous factors (fire area, combustion type, season and wind speed) that make it challenging to accurately quantify the methane released by forest fires [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, data from the Japanese Greenhouse Gases Observing Satellite (GOSAT) revealed that the global monthly mean CH 4 concentration reached 1873 ppb in March 2023, with a growth rate of 15 ppb year −1 from March 2022 to March 2023 (https://www.gosat.nies.go.jp/recent-global-ch4.html (accessed on 6 July 2023)). Reducing methane emissions can be considered an effective way to quickly mitigate climate change because of methane's shorter lifetime than CO 2 [11]. However, the estimation of methane emissions is influenced by numerous factors (fire area, combustion type, season and wind speed) that make it challenging to accurately quantify the methane released by forest fires [12].…”
Section: Introductionmentioning
confidence: 99%